2022
DOI: 10.1016/j.tifs.2021.12.033
|View full text |Cite|
|
Sign up to set email alerts
|

Evidences and perspectives of the use of probiotics, prebiotics, synbiotics, and postbiotics as adjuvants for prevention and treatment of COVID-19: A bibliometric analysis and systematic review

Abstract: Background Coronavirus disease-19 (COVID-19) is an infectious disease transmitted by the virus responsible for the severe acute respiratory syndrome 2 (SARS-CoV-2). Scope and approach This review aimed to provide insights and perspectives for the use of probiotics, prebiotics, synbiotics, and postbiotics related to prevention/treatment and/or modulation of the microbiota in COVID-19 patients. Eighty-four studies published in the Scopus database from the onset of the pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 96 publications
0
56
0
2
Order By: Relevance
“…Improving intestinal microecology is expected to become an adjuvant treatment for COVID-19 (Hu et al, 2021), thus improving the body's immunity and promoting recovery. A bibliometric analysis of 84 scientific studies on microecological interventions with COVID-19 showed that probiotics or prebiotics could enhance resistance to COVID-19 infection, reduce disease duration and symptoms by strengthening the mucosal barrier and modulating the host immune system, as well as strengthening the gut-lung axis (Xavier- Santos et al, 2022). The effect of probiotics on the treatment of COVID-19 has also been widely explored.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…Improving intestinal microecology is expected to become an adjuvant treatment for COVID-19 (Hu et al, 2021), thus improving the body's immunity and promoting recovery. A bibliometric analysis of 84 scientific studies on microecological interventions with COVID-19 showed that probiotics or prebiotics could enhance resistance to COVID-19 infection, reduce disease duration and symptoms by strengthening the mucosal barrier and modulating the host immune system, as well as strengthening the gut-lung axis (Xavier- Santos et al, 2022). The effect of probiotics on the treatment of COVID-19 has also been widely explored.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…In another study, a four-strain probiotic composition was associated with a significant increase in complete viral and symptomatic remission by day 30 in COVID-19outpatients. Some other studies on probiotics supplementation in COVID-19 patients with diarrhea showed that disease duration and gastrointestinal symptoms, such as abdominal distension, nausea and vomiting, were significantly improved [ 77 ]. Moreover, supplementation with Ligilactobacillus salivarius MP101 in elderly patients who tested positive for SARS-CoV-2 significantly decreased the concentrations of fecal BAFF/TNFSF13B, APRIL/TNFSF13, chitinase 3-like 1, IL32, IL34, gp130/sIL-6Rb, sTNF-R1 and sTNF-R2, which is consistent with amelioration of intestinal inflammation [ 78 ].…”
Section: Therapeutic Approaches Targeting the Gut Barriermentioning
confidence: 99%
“…Many reports have described the potential therapeutic effects of probiotics, such as enhancement of the innate immune function, reduction of cholesterol levels, and treatment of gastrointestinal diseases (Bron et al, 2017;Han et al, 2020;Miremadi et al, 2014;Gibson et al, 2017). Prebiotic compounds are non-digestible and non-viable food ingredients, which are selectively processed by probiotics as energy sources to enhance their activity or growth (Fahimdanesh et al, 2013;Xavier-Santos et al, 2022). The synergy between probiotics and prebiotics in synbiotic foodstuffs has been confirmed in many studies (Homayouni et al, 2008;Markowiak & Śliżewska, 2017;Mohanty et al, 2018).…”
Section: Introductionmentioning
confidence: 98%